2021
DOI: 10.1055/a-1686-9620
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for Drug Repurposing of Serotonin Reuptake Inhibitors: Potential Uses in Inflammation, Infection, Cancer, Neuroprotection, and Alzheimer’s Disease Prevention

Abstract: Serotonin reuptake inhibitors (SRIs) are safe and widely used for a variety of indications including depressive disorders, anxiety, and chronic pain. Besides inhibiting the serotonin transporter, these medications have broad-spectrum properties in many systems. Their roles have been studied in cancer, Alzheimer’s disease, and infectious processes. The COVID-19 pandemic highlighted the importance of drug repurpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…Selective serotonin reuptake inhibitors (SSRIs) have been mainstays of psychopharmacology for over 30 years with beneficial effects in major depressive disorder (MDD), anxiety disorders and complex syndromes such as obsessive-compulsive disorder (OCD) [ 1 ]. Effects in psychiatric illnesses are thought to reflect, at least in part, well-known effects on serotonin transporters (SERTs) and changes in serotonin levels in innervated regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selective serotonin reuptake inhibitors (SSRIs) have been mainstays of psychopharmacology for over 30 years with beneficial effects in major depressive disorder (MDD), anxiety disorders and complex syndromes such as obsessive-compulsive disorder (OCD) [ 1 ]. Effects in psychiatric illnesses are thought to reflect, at least in part, well-known effects on serotonin transporters (SERTs) and changes in serotonin levels in innervated regions.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, SSRIs also have actions independent of serotonin that could contribute to therapeutic efficacy. These latter effects include modulation of neuroinflammation, autophagy, and intracellular stress [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mazza recently showed that "COVID depression" may be particularly responsive to SSRIs, suggesting that these drugs may have a role in reducing the substantial morbidity of post-COVID neuropsychiatric syndromes [3]. Serotonin reuptake inhibitors (SRIs) have manifold effects on human physiology, including anti-inflammatory and neurorestorative effects in some studies [4]. Some SRIs have secondary molecular targets, such as the sigma-1 receptor, which motivated our repurposing of fluvoxamine (a strong activator of this receptor) for acute COVID-19.…”
Section: Dear Editormentioning
confidence: 99%
“…As their name implies, the predominant mechanism of action is selective serotonin reuptake inhibition, taking into account the monoaminergic hypothesis, while also expressing their effects on noradrenaline, dopamine, and other neurotransmitter systems. They are indicated and widely used in clinical practice for the treatment of depression (unipolar and bipolar), anxiety disorders, personality disorders, dementia, insomnia, addiction, neuropathic pain, cancer, and even psychosis, etc., and currently SSRI repurposing is very attractive, focusing on immunomodulatory, antiproliferative, and neuroprotective activity ( 18 ). Particular attention has been paid to the possible anti-inflammatory properties of SSRIs, which may be useful, although adverse effects have been warned for initial prescription and long-term use.…”
Section: Introductionmentioning
confidence: 99%